Pure squamous cell carcinoma of the gallbladder in a patient with perforated calculus cholecystitis - Nicol, Alice V.; Y. S. N., Jessica; Colbran, Rachel (International Surgery Journal, 2022)
Gallbladder carcinoma is one of the most common and aggressive malignancies to arise from the biliary tract. However, pure squamous cell carcinoma (SCC) originating from the gallbladder is exceptionally rare, reported to represent less than 1% of all malignancies. An 89-year-old Australian male presented with symptoms and imaging consistent with acute calculus cholecystitis. After failed conservative management he underwent a subtotal cholecystectomy. Diagnosis on histopathological examination demonstrated SCC of the gallbladder. This case highlights the importance of considering gallbladder malignancy including rare histological subtypes such as SCC in patients presenting with symptoms consistent with benign gallbladder disease particularly in the elderly population.